Traditions and Innovations at the International Scientific and Practical Conference of Students, Postgraduates and Young Researchers “Psychology of the XXI Century”: An Event Report - N.A. Medina Bracamonte; O.O. Gofman; M.A. Nedoshivina; P.A. Rystakova (Психологическая наука и образование)
Traditionally, annual student and youth conferences are included in the process of studies at higher education institutions. They are implemented in order to develop students’ professional competencies and soft skills, as well as to provide future specialists with career orientation opportunities. This report is devoted to the international scientific and practical conference “Psychology of the XXI century: A Kaleidoscope of Discoveries”, which was dedicated to the 300th anniversary of Saint Petersburg State University. The conference became an event for students, postgraduates, and young researchers, it was a space for transferring knowledge and experience from the leading scientists to future specialists, and for discussing new theories, methods and practices of psychological support. About 400 students, including undergraduates, graduate students and young scientists, presented their reports at the Faculty of Psychology of Saint Petersburg State University, the total number of participants in various events almost reached a record of 1000 people. They were representatives of various scientific schools and areas of psychology from Saint Petersburg, Moscow, many other regions of Russia, and other countries (Republic of Belarus, Kazakhstan, India, China, The Netherlands). In addition to the classic formats (sections, round tables, master classes), the conference used innovative approaches: interactive sessions, microconferences, topics and sections based on interests, gamification, and real-time feedback. This event received a positive response and became the start for many new projects.